Immobilization of pectinmethylesterase from acerola (Malpighia glabra L.) in porous silica - de Assis, S. A.; Trevisan, H. C.; Mascarenhas, O. M.; Oliveira, F. (Kluwer Academic Publ, 2003)
The total and partially purified enzyme pectinmethylesterase from acerola fruit was covalently immobilized on porous silica particles. These efficiency values were 114% for the total PME and 351% for the partially purified PME. In both forms the immobilization resulted in compounds with high thermal stability.
Keywords: acerola; immobilization; kinetic characterization; pectinmethylesterase; purification